CHEMICAL CHARACTERIZATION OF JATROPHA OIL STORED OVER A PERIOD OF TIME AND ANALYSIS OF ITS PRESSED CAKE - Ananias Ribeiro, Roberto; Mota Nobre Queiroz, Maria das Graças; Alves, Vera Lúcia; Rocha Bernardino de Almeida Prata, Emille; Soares Barbosa, Érica (Revista Unimontes Científica, 2020)
Objective: In this paper, the chemical properties of Jatropha oil and cake were investigated in order to determine the characteristics this plant. Methods: A mechanical expeller was used to obtain oil which was filtered and degummed with phosphoric acid. Jatropha oil and cake were characterized by chemical analysis. Results: Initially, lower values in measurement of acid, iodine, saponification and peroxide values were obtained. After five months of storage, modifications occurred in the oil so that the values increased, demonstrating oil oxidation. Jatropha cake presented an amount of crude fiber and crude protein equals to 21.1 and 20.9 (%w/w), respectively, and mineral elements, Ca, Mg and P, in relatively high amounts, 0.42, 0.54 and 0.71 (%w/w), respectively. Conclusions: Crude Jatropha oil presented low acid and peroxide values